Neotropical sisterhood: new species of Gyrodactylus von Nordmann, 1832 (Platyhelminthes: Monogenea) infecting Rhamdia guatemalensis and Rhamdia laticauda (Siluriformes: Heptapteridae) in Mexico. (14th February 2023) - García-Vásquez, A.; Pinacho-Pinacho, C.D.; Guzmán-Valdivieso, I.; Calixto-Rojas, M.; Rubio-Godoy, M.
Abstract: We describe two new species of monogenean parasites of the genus Gyrodactylus von Nordmann, 1832 infecting Neotropical catfishes (Siluriformes) in southern Mexico: Gyrodactylus chulini n. sp. from 'chulín', Rhamdia laticauda collected in Oaxaca; and Gyrodactylus juili n. sp. from 'juil', Rhamdia guatemalensis from Veracruz. Morphologically, both new taxa are similar to Gyrodactylus spp. infecting catfishes (Siluriformes) in South America. Sequences of the internal transcribed spacers (ITS1-5.8S–ITS2 rDNA), the D2+D3 domains of the large ribosomal subunit (28S rDNA) and the cytochrome oxidase II (COII) gene were obtained from multiple parasite specimens and analysed using Bayesian inference. Phylogenetic hypotheses using ITS rDNA and COII genes, recovered two new Gyrodactylus species from Rhamdia spp.: G. chulini n. sp.; and Gyrodactylus juili n. sp., which are sister species to Gyrodactylus lilianae, a parasite of Rhamdia quelen in Brazil, and show strong affinity to other gyrodactytlids infecting Neotropical catfishes. This suggests that these new taxa, the first gyrodactylids described from Rhamdia spp. in Mexico, co-migrated to Tropical Middle America with their Neotropical catfish hosts, after the emergence of the Isthmus of Panama.